Design and Simulation of Automatic Temperature Control and Alert System Based PIC16F887 - Jabbar Shaati Jahlool (International Journal of Informatics and Communication Technology (IJ-ICT), 2017)
In this research, the design and simulation of an automatic system for temperature control using embedded system in order to automatically control of multi appliances depend on the temperature value. The appliances will be controlled are ventilation, cooling, heating and alert. this is an order to avoid or reduce to human intervention and increase system reliability. An important feature of this automation process is to reduce or eliminate the possibility of relying on the human factor operator for industries, warehouses and laboratories, and to improve working and performance environments. The system in this paper used the microcontroller PIC16F887 as the central control unit, LM35 temperature sensor as a temperature source,16x2 liquid crystal display (LCD) as indicator to display the different system working status an addition to some of drivers, relay and light emitting diodes (LED) as indicators to display the corresponding working appliance driver. The implementation and simulation of the system work has been achieved by using proteus professional software v8.0 and mikroc pro for pic v .6.6.1 software to write the equivalent program and generate .hex file for system working. The result shows in figures 5, 6, 7, and 8 that explain the system working cases